1999
DOI: 10.1039/a808747d
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and mesomorphic properties of 2,2′,3-tri- and 2,2′,3,3′-tetra-fluoro-1,1′∶4′,1″-terphenyls for high dielectric biaxiality ferroelectric liquid crystal mixtures

Abstract: Liquid crystalline 1,1Ј : 4Ј,1Љ-terphenyls with three and four lateral fluoro substituents and alkyl or alkoxy substituents in the 4-and 4Ј-positions have been synthesised. Synthetic strategies employed were convergent and involved the use of arylboronic acids and aryl halides in palladium-catalysed cross-coupling reactions. These syntheses are of particular interest because issues of selective metallation (at positions ortho to a fluoro substituent) and selective coupling reactions (bromo versus iodo sites) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…The group reported that the larger this distance, the larger is the possibility of the formation of a ferroelectric liquid crystal [13]. Trifluorination and tetrafluorination of such cores have also recently been reported [14][15][16].…”
Section: Design Of the Compoundmentioning
confidence: 98%
“…The group reported that the larger this distance, the larger is the possibility of the formation of a ferroelectric liquid crystal [13]. Trifluorination and tetrafluorination of such cores have also recently been reported [14][15][16].…”
Section: Design Of the Compoundmentioning
confidence: 98%
“…The inherently high liquid crystal phase stability of terphenyls allows for the introduction of a third lateral fluoro substituent, and still generates a smectic C phase to a usefully high temperature (compound 33). When next to the original two fluoro substituents, the third fluoro substituent enhances the dielectric anisotropy, and yet the viscosity is reduced [25].…”
Section: Lateral Fluoro Substituentsmentioning
confidence: 99%
“…During the late 1980s and early 1990s, much research was conducted in the area of generating materials for ferroelectric applications, and one of the largest programmes involved the synthesis of ferroelectric host materials and chiral dopants to generate ferroelectric mixtures of high dielectric biaxiality [49][50][51][52][53][54][55][56]. In order to achieve this goal host materials of very high negative dielectric anisotropy were required, and this was best achieved by the use of materials with two lateral fluoro substituents inherently fixed on one side of the molecule (e.g., compound 47) [49].…”
Section: Chiral Induction In Mesophases Generated From Achiral and Ramentioning
confidence: 99%